Persepsi Pengguna Pedestrian di Koridor Jalan Pierre Tendean dan Jalan Sam Ratulangi - Arif, Nugrah Rhisandy; Egam, Pingkan Peggy; Prijadi, Rachmat (Fraktal : Jurnal Arsitektur, Kota dan Sains, 2024)
Jalan Pierre Tendean and Jalan Sam Ratulangi are the main roads in Manado City which are classified as primary arterial roads in Manado City. Due to the status of these two roads, quite a few pedestrians pass through the pedestrian paths on both roads. This research aims to identify the condition of pedestrian paths on Jalan Pierre Tendean and JalanSam Ratulangi and to determine the perceptions of pedestrians who use pedestrian path facilities on these two road corridors. To determine the perceptions of pedestrians who pass this road, a questionnaire was used which was distributed to respondents and measured using a Likert scale. To differentiate the condition of pedestrian paths, researchers divided the two roads into five segments. Based on the research results, the best pedestrian conditions were found in Segments I and II on Jalan Pierre Tendean and from the research results, good scores were in Segments I and II, while Segments III, IV and V received quite good scores.